2015
DOI: 10.1590/s1413-65382115000100004
|View full text |Cite
|
Sign up to set email alerts
|

Possibilidades da Tutoria de Pares para Estudantes com Deficiência Visual no Ensino Técnico e Superior

Abstract: a inclusão escolar pode trazer benefícios incontestáveis para o desenvolvimento da pessoa com deficiência, desde que sejam realizadas adequações e adaptações na dinâmica escolar e nas propostas pedagógicas a fim de atender as necessidades educacionais dos mesmos. Estudos sobre teorias e práticas que contribuam para uma educação inclusiva e de maior qualidade passaram a ser o desafio dos pesquisadores e profissionais da área. Desse modo, esse estudo objetivou analisar e descrever a percepção de estudantes com d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
2
0
8
Order By: Relevance
“…In the SciELO platform, 39 published studies were found with themes related to accessibility and/or inclusion in higher education. Within this theme, the studies focused on different specificities: teacher training to attend students with disabilities in higher education (Reis, Eufrásio and Bazon, 2010); the right to inclusion in higher education (Araujo, 2017); inclusion specifically of students with visual disabilities (Fernandes and Costa, 2015;Regiani and Mól, 2013); inclusion and accessibility specifically of students with hearing disabilities (Bisol et al, 2010;Fernandes and Moreira, 2017;Martins and Napolitano, 2017;Mesquita, 2018); inclusion in higher education (Almeida and Ernica, 2015;Calheiros and Fumes, 2016;Facci, Silva and Souza, 2018;Nozu, Bruno and Cabral, 2018;Oliveira, Gonçalvez and Oliveira, 2016;Poker, Valentim and Garla, 2018); normalization, access legitimacy, participation, and formation (Cabral and Melo, 2017); accessibility in higher education (Silva and Ferreira, 2017); permanence of students with disabilities (Maciel and Anache, 2017); admission and permanence (Castro and Almeida, 2014;Moreira, Bolsanello and Seger, 2011); accessibility and permeance (Garcia, Bacarin and Leonardo, 2018); centers of accessibility in the universities (Ciantelli andLeite, 2016;Ciantelli, Leite and Nuernberg, 2017;Melo and Araújo, 2018); attention to diversity in higher education (Martos-García and Valencia-Peris, 2016); mapping of students in special education (Lourenço and Battistella, 2018); survey on the number of PWD enrolled in higher education (Duarte et al, 2013); participation of students with disabilities in higher education (Gesser and Nuernberg, 2017); meanings of inclusion through students' perspectives (Almeida and Ferreira, 2018); satisfaction evaluation of students with disabilities (Guerreiro, Almeida and Silva Filho, 2014;...…”
Section: Introductionmentioning
confidence: 99%
“…In the SciELO platform, 39 published studies were found with themes related to accessibility and/or inclusion in higher education. Within this theme, the studies focused on different specificities: teacher training to attend students with disabilities in higher education (Reis, Eufrásio and Bazon, 2010); the right to inclusion in higher education (Araujo, 2017); inclusion specifically of students with visual disabilities (Fernandes and Costa, 2015;Regiani and Mól, 2013); inclusion and accessibility specifically of students with hearing disabilities (Bisol et al, 2010;Fernandes and Moreira, 2017;Martins and Napolitano, 2017;Mesquita, 2018); inclusion in higher education (Almeida and Ernica, 2015;Calheiros and Fumes, 2016;Facci, Silva and Souza, 2018;Nozu, Bruno and Cabral, 2018;Oliveira, Gonçalvez and Oliveira, 2016;Poker, Valentim and Garla, 2018); normalization, access legitimacy, participation, and formation (Cabral and Melo, 2017); accessibility in higher education (Silva and Ferreira, 2017); permanence of students with disabilities (Maciel and Anache, 2017); admission and permanence (Castro and Almeida, 2014;Moreira, Bolsanello and Seger, 2011); accessibility and permeance (Garcia, Bacarin and Leonardo, 2018); centers of accessibility in the universities (Ciantelli andLeite, 2016;Ciantelli, Leite and Nuernberg, 2017;Melo and Araújo, 2018); attention to diversity in higher education (Martos-García and Valencia-Peris, 2016); mapping of students in special education (Lourenço and Battistella, 2018); survey on the number of PWD enrolled in higher education (Duarte et al, 2013); participation of students with disabilities in higher education (Gesser and Nuernberg, 2017); meanings of inclusion through students' perspectives (Almeida and Ferreira, 2018); satisfaction evaluation of students with disabilities (Guerreiro, Almeida and Silva Filho, 2014;...…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as diversas práticas educacionais, é possível citar a tutoria de pares, que consiste no apoio mútuo de estudantes no processo do desenvolvimento acadêmico e social. Em um estudo entre estudantes com deficiência visual (Fernandes & Costa, 2015), a tutoria de pares apresentou-se como uma estratégia promissora para dar apoio à inclusão desses estudantes no ensino técnico e superior. Estratégias como essa podem contribuir para o processo de inclusão no mundo do trabalho, articulando educação e trabalho.…”
Section: Conclusõesunclassified
“…Nesse cenário, sabe-se que os estudantes são privados de muitas oportunidades, pois a forma como as universidades estão estruturadas, física e pedagogicamente, interfere na dinâmica de estudo dos discentes, podendo criar entraves capazes de interromper a sua trajetória acadêmica. O acesso aos materiais didáticos, portanto, é fundamental no processo formativo do estudante na instituição de ensino, a fim de garantir a autonomia desse público e a sua inserção nos diversos ambientes que propiciem o aprendizado (Fernandes & Costa, 2015). Este aspecto também foi destacado por Castro & Almeida (2014), em estudo para conhecer as ações realizadas pelas instituições de ensino superior voltadas para o atendimento dos estudantes com deficiências.…”
Section: Recursos Materiais Para Os Estudantes Com Deficiência Visualunclassified